Accumulation of heavy metals by Conyza bonariensis (L.) Cronq in the upper basis of the river Bogotá (2020)
The shedding of wastes along the length of the river Bogotá causes environmental problems and harms the health of the people who live nearby. At the current time, as it passes through the municipality of Chocontá Colombia, it receives discharges of the wastes from the industries in that region which contaminate soils at the same time that they harm agricultural production and therefore the communities who live on the banks of the river. This study analyzes the presence of the metals Cr. Pb. Cd Co and As in specimens of Conyza bonariensis (L.) Cronq. gathered along the western bank of the upper basin of the river Bogotá between the towns of Villapinzón and Chocontá, a highly contaminated area due to the presence of tanning industries and in the town of Usme in the environs of the páramo (high Andean moor) of Sumapaz (Department of undinamarca, Colombia). With the data obtained from soil analyses, we were able to conclude that the chrome in the area of Villapinzón is 457% higher than that found in the soil of Usme. The root and stem of the Conyza bonariensis species collected in the region of Villapinzón also showed a higher bio-accumulation of chrome: 6342% and 2682%. respectively, higher than those in the region of Usme. The Pb. Cd. Co and As in the soils were likewise higher in the former by a percentage of between 118% and 148%, as was the bioaccumulation in different organs of the plants (between 111% and 270%), figures which indicate to us that the Conyza bonariensis is a species with potential uses for processes involving the phytoremediation of soils.